Pesantren Al-Khairaat of Gorontalo: Hadrāmī Tradition and Habāib Domination - Zaenuri, Ahmad; Yusuf, Habibie (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Al-Khairaat is an Islamic Boarding School founded by a charismatic cleric of Hadramaut descent, Sayyid Idrus bin Sālim Al-Jufrie in Palu, Central Sulawesi. Since its establishment in 1930, more than 500 branches of Al-Khairaat schools have spread in the central, northern, southeast, and western parts of Sulawesi Island to Gorontalo area. The development of Al-Khairaat became interesting because the school curriculum represents a pattern of Hadrāmī tradition offered in society (ahwal). Besides, the charismatic dominance of Sayyid Idrus bin Sālim Al-Jufrie as a descendant of the Prophet became an appeal in gaining public trust in Al-Khairaat. This research aimed to analyze the extent of how the Hadrāmī tradition applied and the influence of Sayyid Idrus Bin Sālim Al-Jufrie as a descendant of the Prophet to develop Al-Khairaat boarding school. The field research was carried out using an ethnographic method. The research results showed that the tradition of Hadrāmī in the form of wirid, dhikr, and shalawat had become an appeal. It conforms to the social conditions of Gorontalo people, who appear to be traditionalists in the practice of religion and some of their people are similar to the rituals of urban sufism. In addition, people who want their children to become proficient in religion often claim that Al-Khairaat can deliver these values. As for the dominance of habāib, it is more noticeable in culture, social, and symbol in the context of a high appreciation of it in society's social stratification and even things considered non-scientific.